The analysis of taboo words in “Cek Toko Sebelah (2016)” movie - May Lita Dinda Adrio (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2022)
The purpose of this article is to identify kind of taboo words found in Cek Toko Sebelah Movie. This article using descriptive qualitative research method, with data collection techniques, namely documentation and the data analyze use Miles and Huberman (1992) theory. There are 7 kinds of taboo according to Timothy Jay (1996) cursing, profanity, blasphemy, obscenity, sexual harassment, vulgar language, and insult. The researcher found 3 kinds of taboo word in Cek Toko Sebelah movie, namely cursing, sexual harassment, and insult. The use of cursing in this film is intended to curse someone or express their emotions. Sexual harassment is also found in this movie both implicitly and explicitly. The most common type found in this movie is insults that are used to hurt others, but not all insults in this movie aim to insult, there are some that are used as expressions of familiarity and indifference.